Documenting the past: performativity and inter-subjectivity in the memory project. Issue 3 (1st September 2016) - Meng, Jing
ABSTRACT: A growing number of Chinese independent documentaries about history and memory have emerged since 2000. This paper explores several documentaries of the Folk Memory Project: Wu Wenguang's Treatment ( Zhiliao, 2010) and Zhang Mengqi's Self-Portrait series: Self-Portrait with Three Women ( Zihuaxiang he san ge nüren, 2010), Self-Portrait: at 47 km ( Zihuaxiang: 47 gongli, 2011), Self-portrait: Dancing at 47 km ( Zihuaxiang: 47 gongli tiaowu, 2012) and Self-Portrait: Dreaming at 47 km ( Zihuaxiang: 47 gongli zuomeng, 2013). Drawing on concepts of performativity and inter-subjectivity, I argue that Wu's and Zhang's documentaries highlight the subjective and dialogical dimensions of documentation and memory, making visible their techniques for dealing with past events in ways which invite further engagement and reflection. Wu's and Zhang's documentaries have enabled the utterance and affective sharing of muted memories. Moreover, these Chinese independent documentaries also represent a shift in style from austere, long-take realism toward more experimental, performative and self-reflexive works.